Larvae of forensically important flies associated with rabbit carcasses placed in a closed room in Kuching, Sarawak / Robin Maramat ... [et al.] - Maramat, Robin; Ibrahim, Norliza; Othman, Marlini; Abdul Rahim, Nor Aliza (Faculty of Medicine, 2021)
Introduction: This is the first report on insects associated with rabbit carcasses in indoor environment in Kuching, Sarawak. Methods: This study was conducted on June till August of 2016. Rabbit carcasses (Oryctolagous cuniculus) which were used as the animal model, were placed inside a dark room in a building at Forensic Medicine Department in Sarawak General Hospital. The fly larvae infesting on the carcasses were collected until the decomposition process completed. Throughout the 15 days of experiment, the fly larvae were sampled on the carcasses indoor at 28.9 ± 0.3 °C and 69.6 ± 1.0% humidity. Results: The fly larvae activity was observed during the active decay stage and was identified as Synthesiomyia nudiseta (van der Wulp, 1883) (Diptera: Muscidae) and Sarcophaga spp. (Diptera: Sarcophagidae). Only these two species were found co-existing on the carcasses. Conclusions: S. nudiseta and Sarcophaga spp. could be used as an entomological evidence involving indoor cases in Kuching, Sarawak because both species were dominant and active carcass decomposers in indoor environment.